(untitled) (Agricultural Engineering, 2017)
Short review of grassland restoration techniques has been made with emphasis on the application of newly developed wide-strip overseeding aggregate. Machines currently available on the market are not suitable for all types of soil and grassland conditions. Vredo seeder is useless on muck soils, while Moore aggregate requires herbicide application. Therefore it is not to be applied in organic farming. Construction designated in ITP Kłudzienko (wide-strip overseeder) is a very economical and effective, possible to be used also on muck soils and without assistance of any chemicals. Operation of the machine consists of ‘milling’ of wide (about 10 cm) strips of sod and overseeding of mineral fertilizers and seeds of grasses, legumes and herbs. Cultivator for soil ‘milling’ strips is driven by the tractor PTO. By changing the spacing of strips, an oversown area can be resized from 20% to 40%. The effect of overseeding, evaluated next year exposed the increase of hay yield from 0.8 to 1.2 t·ha-1 of dry matter in the first cut. Such innovative construction is particularly important in dairy farms which are in the need of the best quality feed.